The Aggregation Regularity Effect of Multiarylpyrroles on Their Near‐Infrared Aggregation‐Enhanced Emission Property. Issue 65 (15th October 2020) - Qu, Jiamin; Ren, Fei; Shi, Jianbing; Tong, Bin; Cai, Zhengxu; Dong, Yuping
Abstract: Increasing the quantum yield of near‐infrared (NIR) emissive dyes is critical for biological applications because these fluorescent dyes generally show decreased emission efficiency under aqueous conditions. In this work, we designed and synthesized several multiarylpyrrole (MAP) derivatives, in which a furanylidene (FE) group at the 3‐position of the pyrrole forms donor‐π‐acceptor molecules, MAP‐FE, with a NIR emissive wavelength and aggregation‐enhanced emission (AEE) features. Different alkyl chains of MAP‐FEs linked to phenyl groups at the 2, 5‐position of the pyrrole ring resulted in different emissive wavelengths and quantum yields in aggregated states, such as powders or single crystals. Powder XRD data and single crystal analysis elucidated that the different lengths of alkyl chains had a significant impact on the regularity of MAP‐FEs when they were forced to aggregate or precipitate, which affected the intermolecular interaction and the restriction degree of the rotating parts, which are essential components. Therefore, an increasing number of NIR dyes could be developed by this design strategy to produce efficient NIR dyes with AEE. Moreover, this method can provide general guidance for other related fields, such as organic solar cells and organic light‐emitting materials, because they are all applied in the aggregated state. Abstract : A series of multiarylpyrrole derivatives with near‐infrared emission and aggregation‐enhanced emission features were designed to increase the quantum yield of dyes in solid, which powder XRD data and single crystal analysis elucidated that the different lengths of alkyl chains had a significant impact on the regularity of NIR dyes when they were forced to aggregate or precipitate.